how to decrement and increment loop range 'i' variable in the execution of loop in python -
i new in python , don't know why program not updating 'i' variable when incrementing in execution of loop. len(a) = 10
can see in code incrementing 'i' time after time after increment when comes loop iteration nullifies update made in body of loop. why ? should updated in general , loop execution should less 10. please help.
final_result = 0 a= '3 4 4 5 6' in range(0,len(a)): print('iteration') print('i = ') print(i) if a[i] ' ' , a[i+1] not ' ': if i-1 0: final_result = int(a[i-1]) + int(a[i+1]) += 2 //here goes increment print('1a- m here') print(final_result) print('i = ') print(i) else: final_result = final_result + int(a[i+1]) += 2 //here goes increment print('1b- m here') print(final_result) elif a[i] ' ' , a[i+1] ' ': if i-1 0: final_result = int(a[i-1]) - int(a[i+1]) += 3 //here goes increment print('2a- m here') print(final_result) else: final_result = final_result - int(a[i+2]) += 3 //here goes increment print('2b- m here') print(final_result) print('i = ') print(i) print(final_result)
so several things:
- use
while
loop. - initialize
i = 0
- increment
i += 1
when none of conditions match - comments in python written
# comment
, not// comment
.
example:
final_result = 0 = '3 4 4 5 6' = 0 while < len(a): print('iteration') print('i = ') print(i) if a[i] ' ' , a[i + 1] not ' ': if - 1 0: final_result = int(a[i - 1]) + int(a[i + 1]) += 2 # here goes increment print('1a- m here') print(final_result) print('i = ') print(i) else: final_result = final_result + int(a[i + 1]) += 2 # here goes increment print('1b- m here') print(final_result) elif a[i] ' ' , a[i + 1] ' ': if - 1 0: final_result = int(a[i - 1]) - int(a[i + 1]) += 3 # here goes increment print('2a- m here') print(final_result) else: final_result = final_result - int(a[i + 2]) += 3 # here goes increment print('2b- m here') print(final_result) print('i = ') print(i) else: += 1 print(final_result)
output:
$ python3.4 foo.py iteration = 0 iteration = 1 1a- m here 7 = 3 iteration = 3 2b- m here 3 = 6 iteration = 6 1b- m here 8 iteration = 8 1b- m here 14 14
Comments
Post a Comment